Fluoroquinolone resistance in Campylobacter jejuni and Campylobacter coli from poultry and human samples assessed by PCR-restriction fragment length polymorphism assay. - Yuli Melisa Sierra-Arguello; Thales Quedi Furian; Gustavo Perdoncini; Hamilton L S Moraes; Carlos T P Salle; Laura B Rodrigues; Luciana Ruschel Dos Santos; Marcos José Pereira Gomes; Vladimir Pinheiro do Nascimento (PLoS ONE)
The objective of this study was to determine fluoroquinolone resistance in Campylobacter spp from poultry and human isolates. Forty-one Campylobacter jejuni isolates (30 of poultry origin and 11 of human origin) and 11 Campylobacter coli isolates (10 of human origin and 1 of poultry origin) were examined for ciprofloxacin, norfloxacin, and nalidixic acid resistance using the minimal inhibitory concentration (MIC) method. Thereafter, the isolates were analyzed by PCR-Restriction Fragment Length Polymorphism (RFLP) assay for detection of Thr-86 mutation. Finally, DNA sequencing was performed for confirmation of gyrA gene mutation. A complete correlation was observed between MICs, PCR-RFLP assay, and sequencing. The results revealed high quinolone resistance rates for C. jejuni (100%) and C. coli (100%) isolates obtained from poultry and moderate resistance for C. jejuni (9.1%) and C. coli (40%) samples of human origin. A mutation in codon 86 of the gyrA gene with a Thr-to-Ile substitution is reported to be the main cause of high resistance to quinolones. This mutation can be analyzed by PCR-RFLP assay, which has been proven to be a simple and fast method for the detection of fluoroquinolone resistance in Campylobacter spp.